Pengaruh Dosis Pupuk Organik Cair Tanaman Kacang Hijau (Vigna radiata L.) dan Komposisi Media Tanam terhadap Pertumbuhan Bibit Mindi (Melia azedarach L.) - Nurheni Wijayanto; Kareena Klauta Kardiyono (Jurnal Silvikultur Tropika, 2020)
Combination mindi and mung bean is one of agroforestry in community forest. Mung bean waste is a potential organic material that can be used as liquid organic fertilizer. The research aims to test the effect of different mung bean liquid organic fertilizer doses and several media compositions of the mindi growth. This research used Completely Randomized Design (CRD) with two factors. The liquid organic fertilizer of mung bean used several dose, namely 0 ml / liter of water, 200 ml / liter of water, 300 ml / liter of water, and 400 ml / liter of water to each plant. In addition, media compositions that are used, namely: 1. combination of soil, cocopeat and husk, 2. combination of soil, sand, and cocopeat, and 3. combination of soil, sand, and husk. The results showed that treatment of 400 ml liquid organic fertilizer of mung bean per liter of water and combination of cocopeat, soil, and sand produce the best height. Treatment of 300 ml liquid organic fertilizer of mung bean per liter of water and combination of cocopeat, soil, and sand or with mixed media chaff, dirt and sand produce the best diameter. Keywords: Liquid organic fertilizer, media composition, Melia azedarach L., mung bean